Ebola Virus Disease: A Deadly Hemorrhagic Fever - Akram, Muhammad; Mahmood, Abid; Umaru, Isaac John; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben (African Journal of Clinical Medicine and Pharmacy Research, 2025)
The West African pandemic of 2014–2016 exposed the catastrophic effects of inadequate health systems and delayed responses, serving as a wake-up call for the international community. The Zaire virus is the most virulent of the six known Ebolavirus types and has caused the majority of human outbreaks, including the historic West African epidemic that lasted from 2014 to 2016. Depending on the virus type, host characteristics, and the availability of palliative care, Ebola can have high case fatality rates of over 50%. The potential for quick transmission, high mortality, and severe social and economic disruptions makes EVD a serious public health concern. It is believed that the Ebola virus starts in a zoonotic reservoir, most likely animals. Once in the human population, the virus is disseminated via direct contact with contaminated fomites and people. If proper infection prevention and control procedures are not implemented, family members, caregivers, and healthcare personnel are especially vulnerable. EVD manifests as a generic febrile disease that includes abrupt onset of fever, tiredness, headache, sore throat, and muscular discomfort after This is frequently followed by rash, diarrhea, vomiting, and worsening renal and liver function. Viral RNA can be found using RT-PCR, antigen capture assays, or virus isolation from blood or other clinical specimens to confirm the diagnosis. Early case identification and isolation, contact tracking, and quarantining exposed persons are essential for outbreak containment because of its high contagiousness and quick spread. The main goals of supportive treatment are electrolyte balance, fluid replenishment, and problem-solving. With the discovery of vaccinations, EVD prevention has greatly improved. Due to its excellent effectiveness, the rVSV-ZEBOV vaccine (Ervebo), a recombinant live attenuated vaccine based on the vesicular stomatitis virus, is being utilized in ring vaccination techniques during epidemics. One of the main pillars of responses to recent outbreaks is the vaccination of frontline staff and high-risk contacts.